Calistenia y fortalecimiento físico en deportistas de Judo de 9 a 12 años - Cayambe Quishpi, Jeyson Ariel (2022)
The present investigation consisted in proposing a calisthenics program oriented to physical strengthening in children from 9 to 12 years old, 20 judo athletes of the study population were evaluated by means of a physical test, from which a control and intervention group was completed, which will measure the physical level in which they are. The test was used as a technique and as an instrument the talent selection test of Ecuador, divided into 3 tests, elbow push-ups, sit-ups and long jump s/c, according to the results will be scored from 1 to 10, the points obtained in each test will be added, the result will be placed according to the rating scale from Level I to Level IV. The Post-Test of the control group showed an average of 10.1 obtaining a Level I evaluation and the Post-Test of the intervention group showed an average of 15.6 obtaining a Level II evaluation. The T-Student was performed, where the Sig. (bilateral) in the test is .003 less than .05 of the P value, it is determined that there is a significant difference between the two repeated measures, the alternative hypothesis is accepted, concluding that there is inequality of means between the results of the tests, obtaining better results in the Post-Test of the intervention group. It was concluded that a calisthenics program focused on physical strengthening significantly improves the results, this means that there is a significant association between physical strengthening and the calisthenics program.